Antecedents of employees' job performance: a case of Dewan Bahasa dan Pustaka / Nor Fazalina Salleh ... [et al.] - Salleh, Nor Fazalina; Ramlee, Nur Atiqah Zakiyyah; Abd Rahim, Lina Nadia; Asnawi, Nini Hartini; Ghazali, Norfazlina; Sahidan, Shuhada (Universiti Teknologi Mara Selangor, 2022)
The company's productivity relies on the performance of its human resources. Many scholars are interested in job performance because of its significance to business performance. Hence, this study is attempted to investigate factors that motivate the employees' job performance. The study was conducted among 102 Dewan Bahasa dan Pustaka employees. This cross-sectional study has identified three antecedents, namely reward system, work environment, and career development. Data were gathered via a self-administer questionnaire. Convenience sampling was used as a method to determine the respondent for this study and data collected were analyzed using correlational statistical techniques with the latest version of SPSS software. The result shows that there is a positive relationship between reward systems, work environment, and career development with job performance among employees in the Dewan Bahasa dan Pustaka. For future research, the study proposes to examine other variables such as work-life balance, and workload to measure their relationship with job performance. It is also recommended that other researchers replicate the study in a different research setting, such as obtaining the data from private sectors.